ALL classification using neural ensemble and memetic deep feature optimization - Awais, Muhammad; Ahmad, Riaz; Kausar, Nabeela; Alzahrani, Ahmed Ibrahim; Alalwan, Nasser; Masood, Anum (Frontiers in Artificial Intelligence, 2024)
Acute Lymphoblastic Leukemia (ALL) is a fatal blood disorder characterized by the excessive proliferation of immature white blood cells, originating in the bone marrow. An effective prognosis and treatment of ALL calls for its accurate and timely detection. Deep convolutional neural networks (CNNs) have shown promising results in digital pathology. However, they face challenges in classifying different subtypes of leukemia due to their subtle morphological differences. This work proposes an improved pipeline for binary detection and sub-type classification of ALL from blood smear images. At first, a customized, 88 layers deep CNN is proposed and trained using transfer learning along with GoogleNet CNN to create an ensemble of features. Further, this work models the feature selection problem as a combinatorial optimization problem and proposes a memetic version of binary whale optimization algorithm incorporating Differential Evolution based local search method to enhance the exploration and exploitation of feature search space. The proposed approach is validated using publicly available standard datasets containing peripheral blood smear images of various classes of ALL. An overall best average accuracy of 99.15% is achieved for binary classification of ALL with an 85% decrease of the feature vector, together with 99% precision and 98.8% sensitivity. For B-ALL sub-type classification, the best accuracy of 98.69% is attained with 98.7% precision and 99.57% specificity. The proposed methodology shows better performance metrics as compared to several existing works.